Induced breeding of the riverine catfish Rita rita (Journal of the Bangladesh Agricultural University, 2010)
The paper reports the first incidence of successful induction of breeding in the riverine catfish Rita rita using carp pituitary gland (PG) extract. A breeding trial using four PG doses viz. 80, 100, 120 and 140mg/kg body weight of fish was conducted to optimize the dose of pituitary gland (PG) extract in terms of induction of ovulation in female. The male received a dose of 40mg PG/kg body weight in all cases and was sacrificed for collection of milt. The best performance was shown by the fish treated with 100mg PG/kg body weight in respect of inducing ovulation in females and fertilization and hatching rates of eggs. Keywords: Induced breeding; Rita rita; Ovulation; Fertilization rate; Hatching rate DOI: 10.3329/jbau.v6i2.4835 J. Bangladesh Agril. Univ. 6(2): 361-366, 2008